Agronomic education for nurturing skill development and agripreneurship - Vyas, A K; Jain, N K; Prajapat, Kailash (Indian Farming, 2021)
Despite increase in farm productivity and self-sufficiency in food grains, Indian agriculture is encountering challenges of reducing factor productivity, vulnerability to climate change, resource degradation, etc. in general and decreasing profitability and declining interest of youths in farming at large. Agronomy as a core discipline of agriculture has the capacity to accept these current and future challenges of Indian agriculture to find appropriate sustainable solutions. There is dire need to broaden the vision and redefine the role of present Agronomy to diversify agriculture activities through customized skill development and agripreneurship so as to ensure better options for livelihoods and sustainable development. Agronomy needs to be visualized in broader perspective beyond crop production and it focuses on post-harvest management, quality, value addition, processing and effective marketing of produce through appropriate skill development and agripreneurship. The present situation demands a renewed thrust for enhanced quality and relevance of agricultural education so as to facilitate and undertake human capacity building for developing self-motivated professionals and entrepreneurs in view of the changing scenario of globalization of education, emergence of new areas of specialization and agripreneurship. The agriculture graduates are required to possess professional capabilities and skills to successfully promote start-ups and agripreneurship. Agripreneurship is the need of hour to make agriculture a more attractive and profitable venture. Agripreneurship is not only an opportunity but also a necessity for improving the production and profitability in agriculture and allied sector where agronomy has a pivotal role. There is a greater scope for entrepreneurship in agriculture and this potentiality can be tapped only by effective management of agrielements such as - soil, water, agriinputs, post-harvest issues and market needs. Active involvement of youth in agripreneurship, farm advisory, empowering them with knowledge and skills to serve the society through technology-led business models, incubation models, and value-added services are important to create employment opportunities for the youth in agriculture. All these approaches would help in desired goal of transforming youth from job seekers to job providers. The agronomy education and training can provide all requisite knowledge and skills to develop a successful entrepreneur. Thus, the agriculture sector has a large potential to contribute to the national GDP and simultaneously provide direct employment and income to the larger and vulnerable section of the society.